Analisis Pengaruh Kemiskinan Dan Pengangguran Terhadap Pertumbuhan Ekonomi Di Tapanuli Selatan - Nasution, Fitri Sari Ramdhani; Sahnan, M.; Naeruz, Mila (Universitas Islam Sumatera Utara, 2024)
The problem formulation of this research is whether poverty has an effect on economic growth, and whether unemployment has an effect on economic growth in South Tapanuli Regency . The aim of this research is to find out how the level of poverty and unemployment influences economic growth. This research was conducted in South Tapanuli Regency. The technical analysis of this research is quantitative analysis using classical and multiple linear assumption tests. The data source used in this research is secondary data downloaded via the official website of the Central Statistics Agency ( BPS ), especially data on the number of poverty in South Tapanuli Regency and data on the number of unemployed. and data on economic growth. Based on the results of research that has been conducted, it shows that poverty and unemployment have a positive or significant effect on economic growth in South Tapanuli Regency. It can be seen that the Fcount value is 14.955 and the Sig value. is 0.002. In the F distribution table, the Ftable value obtained at α = 0.05 with df1 ( df regression ) = 2 and df2 ( residual df ) = 3 is 9.5. This shows that the Fcount value ( 14.955 ) Ftable ( 9.55 ) and the Sig value 0.002 0.05. So it can be concluded that H0 is rejected and Ha is accepted, meaning that the poverty level and unemployment rate simultaneously have a significant effect on economic growth in South Tapanuli.The problem formulation of this research is whether poverty has an effect on economic growth, and whether unemployment has an effect on economic growth in South Tapanuli Regency . The aim of this research is to find out how the level of poverty and unemployment influences economic growth. This research was conducted in South Tapanuli Regency. The technical analysis of this research is quantitative analysis using classical and multiple linear assumption tests. The data source used in this research is secondary data downloaded via the official website of the Central Statistics Agency ( BPS ), especially data on the number of poverty in South Tapanuli Regency and data on the number of unemployed. and data on economic growth. Based on the results of research that has been conducted, it shows that poverty and unemployment have a positive or significant effect on economic growth in South Tapanuli Regency. It can be seen that the Fcount value is 14.955 and the Sig value. is 0.002. In the F distribution table, the Ftable value obtained at α = 0.05 with df1 ( df regression ) = 2 and df2 ( residual df ) = 3 is 9.5. This shows that the Fcount value ( 14.955 ) Ftable ( 9.55 ) and the Sig value 0.002 0.05. So it can be concluded that H0 is rejected and Ha is accepted, meaning that the poverty level and unemployment rate simultaneously have a significant effect on economic growth in South Tapanuli